Deicsis In The Drama Script "Laskar Pelangi" By Hanum Khanti Prameshti - Nurlaili Saadah; Nasuha (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
This study aims to determine the deixis in the Laskar Pelangi script by Hanum Kanthi Pramesthi. This study uses a qualitative descriptive method. The object of this study is the Laskar Pelangi drama script by Hanum Kanthi Pramesthi. The aspects observed are the forms of deixis contained in the drama script and its analysis. The data source for this study is the drama script itself. Data collection in this study was carried out using several techniques including observation techniques, reading techniques and note-taking/writing techniques. The research time was carried out flexibly. The results of this study contained 164 deixis. The data is divided into 129 person deixis, 15 place deixis, and 20 time deixis.